Heart depolarization vector locus cardiogram and its clinical diagnostic applications - Nagenthiran, T. (2013)
This study demonstrates the development of the heart depolarization vector locus cardiogram (HPVLC, from limb leads and a modified Einthoven's triangle) as a diagnostic measure of the left ventricular depolarization strength. Our work involves the reconstruction of the "equivalent heart electrical-activity vector (HAV)" for the QRS complex from limb leads voltages of a sample ECG recording, and plotting the progression of the cardiac vector during the QRS complex.